Combination treatment of low fluence photodynamic therapy and intravitreal ranibizumab for choroidal neovascular membrane secondary to angioid streaks in Paget's disease – 12 month results - Prabhu, Varsha V (Medknow Publications, 2011)
Angioid streaks also called Knapp striae are small breaks in the Bruch's membrane and have been reported with a host of systemic diseases. Rupture of streaks or development of secondary choroidal neovascular membrane (CNVM) carries a dismal visual prognosis. We report the successful treatment of CNVM secondary to Paget's disease using low fluence photodynamic therapy (PDT) and intravitreal ranibizumab.